ANALISIS PENERAPAN SISTEM INFORMASI MANAJEMEN DAN KOMPETENSI PEGAWAI SERTA PENGARUHNYA TERHADAP KINERJA PEGAWAI - Suyitno Suyitno (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2017)
The study titled "The study of the influence of the use of information systems and employee competence on the performance of employees in the Board of Industry and Trade Fakfak Regency ", was conducted with the aim to know how the influence of the application of management information systems to employee performance in the Department of Industry and Trade in Fakfak Regency.The research was conducted by survey the use of management information system, the application of competence and its effect on employee performance. Survey is done by observation method and comprehensive interview to respondent. The number of respondents is 40 people who are also employees in Department of Industry and Trade in Fakfak Regency, the data obtained through the questionnaire is then analyzed with the help of SPSS vers 11.5 program. Based on the result of the research, it can be seen that the application of management information system significantly influence the performance of employees at Department of Industry and Trade in Fakfak Regency, with regression coefficient 0,650 (p-value = 0.000). Employee competence significantly affects the performance of employees at Department of Industry and Trade in Fakfak Regency, with a regression coefficient of 0.679 (p-value = 0.000). This shows that the competence of employees, will drive the performance of government agencies directly by 67.9%. Implementation of management information system and employee competence together significantly affect the performance of employees at Department of Industry and Trade in Fakfak Regency of 68.1%.